Micro-founded tax policy effects in a heterogeneous-agent macro-model - Diego d'Andria; Jason DeBacker; Richard Evans; Jonathan Pycroft; Magdalena Zachlod-Jelec (European Commission, Joint Research Centre (JRC), 2019)
Microsimulation models are increasingly used to calibrate macro models for tax policy analysis. Yet, their potential remains underexploited, especially in order to represent the non-linearity of the tax and social benefit system and interactions between capital and labour incomes which play a key role to understand behavioural effects. Following DeBacker et al. (2018b) we use a microsimulation model to provide the output with which to estimate the parameters of bivariate non-linear tax functions in a macro model. In doing so we make marginal and average tax rates bivariate functions of capital income and labour income. We estimate the parameters of tax functions in order to capture the most important non-linearities of the actual tax schedule, together with interaction effects between labour and capital incomes. To illustrate the methodology, we simulate a reduction in marginal personal income tax rates in Italy with a microsimulation model, translating the microsimulation results into the shock for a dynamic overlapping generations model. Our results show that this policy change affects differently households distinguished by age and ability type.
Keywords: H24; H31; D15; D58; 330; computable models; general equilibrium; overlapping generations; taxation; microsimulation models